ОТНОШЕНИЕ ДЕТЕЙ К КУЛЬТУРАМ БЛИЖАЙШЕГО ОКРУЖЕНИЯ В ИНТЕРКУЛЬТУРНОМ ПРОСТРАНСТВЕ: ПСИХОЛОГИЧЕСКАЯ КОНЦЕПТУАЛИЗАЦИЯ - Наталья КИНЧЕВА (Moldova State University, 2018)
Раскрыт научный термин «отношение». Освещено понятийное поле концепции В.Н. Мясищева - отношение и его компоненты. Раскрыта специфика взаимодействий и взаимоотношений детей старшего дошкольного возраста. Анализируются психологические основы формирования позитивного отношения к культурам ближайшего окружения посредством музыкальной деятельности. ATTITUDE OF CHILDREN TO CULTURES OF THE NEAREST SURROUNDING IN INTERCULTURAL SPACE: PSYCHOLOGICAL CONCEPTUALIZATION The article discloses the scientific term "attitude". The conceptual field of the V.N. Myasishchev's conception is attitude and its components. The specificity of interactions and relationships of children of senior preschool age is given. The psychological foundations of the formation of a positive attitude towards the cultures of the nearest surrounding with a help of musical activity are analyzed.